2016
DOI: 10.1002/2016gl069415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the tiger stripes on the deformation of Saturn's moon Enceladus

Abstract: Enceladus is a small icy moon of Saturn with active jets of water emanating from fractures around the south pole, informally called tiger stripes, which might be connected to a subsurface water ocean. The effect of these features on periodic tidal deformation of the moon has so far been neglected because of the difficulties associated with implementation of faults in continuum mechanics models. Here we estimate the maximum possible impact of the tiger stripes on tidal deformation and heat production within Enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 23 publications
6
56
2
Order By: Relevance
“…This is a consequence of the small size of Enceladus, which makes the amplitude of tidal deformation much more sensitive to the ice shell thickness than in larger moons like Europa and Titan, where tidal deformation depends only slightly on the ice shell thickness (Tobie et al, 2005). Soucek et al (2016) have also demonstrated that the presence of faults further enhances the tidal deflections by at least a factor of 2. The resulting stress patterns are much more complex than those predicted from standard tidal deformation models based on a thin-shell approximation and neglecting the presence of faults (e.g., Hurford et al, 2007;Nimmo et al, 2007).…”
Section: Latitude (ºN)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is a consequence of the small size of Enceladus, which makes the amplitude of tidal deformation much more sensitive to the ice shell thickness than in larger moons like Europa and Titan, where tidal deformation depends only slightly on the ice shell thickness (Tobie et al, 2005). Soucek et al (2016) have also demonstrated that the presence of faults further enhances the tidal deflections by at least a factor of 2. The resulting stress patterns are much more complex than those predicted from standard tidal deformation models based on a thin-shell approximation and neglecting the presence of faults (e.g., Hurford et al, 2007;Nimmo et al, 2007).…”
Section: Latitude (ºN)mentioning
confidence: 99%
“…Further details of elastic/viscoelastic support models are beyond the scope of this chapter, but it should be noted that this remains an active area of research (Čadek et al, 2016;Soucek et al, 2016;Hemingway and Mittal, 2017). In particular, it is not yet clear how elastic support of the long-wavelength topography is affected by factors such as lateral variations in the shell's elastic properties (Beuthe, 2008;Čadek et al, 2016, 2017, or the way bending and membrane stresses are transmitted across the SPT given the presence of the major fracture systems (i.e., the Tiger Stripes) in that region (e.g., Soucek et al, 2016).…”
Section: Admittance Analysismentioning
confidence: 99%
“…In a previous study of the topic, Běhounková et al [2017] used the finite-element method (FEM) of Souček et al [2016] to solve for the deformations of an elastic shell with non-uniform thickness, and predicted several tens of GW of tidal heating by assuming a shell of uniform viscosity. This last assumption is not realistic for a conductive shell because viscosity increases by orders of magnitude from the bottom of the shell to the surface; the total power dissipated in the shell is actually much lower.…”
Section: Introductionmentioning
confidence: 99%
“…However, their effective values can significantly decrease in regions that do not transmit stress, such as fractured zones or faults. This property was employed by Souček et al ( 2016 ), who incorporated the tiger stripes in terms of narrow zones that pass vertically through the ice shell, in which the elastic moduli were artificially reduced by several orders of magnitude. Souček et al ( 2016 ) avoided the use of the standard spectral method, which does not allow for a sufficiently high resolution; instead these authors applied the finite element method on an unstructured grid.…”
Section: Introductionmentioning
confidence: 99%